BETON INSTANT TANPA SEMEN DAN TANPA PEMADATAN MANUAL - PRATIKTO PRATIKTO; ANNI SUSILOWATI (Politeknik Negeri Jakarta, 2013)
ABSTRACT The so called self compacting geopolymer concrete can be a response to the weakness of conventional concrete cause the need of cement and compaction process. Global warming caused by greenhouse gas emissions , such as co2 as a result of the use of portland cement can be reduced. Instant concrete will consist of aggregates and a mixture chemical composition of geopolimer in the absence of water. The activator of geopolymer concrete used alkaline solution consisting of sodium hydroxide ( naoh ) and sodium silicate , with fly ash binder . Variation of water binder ratio ( wbr ) from 0.30 , 0.25 and 0.20 combined with superplasticizer of 1% and 2 % . Aggregate to be used is split with a diameter of 10mm and fine aggregate sand. Results are mixed composition : naoh = 1 ; na2sio3 = 2 ; water = 1.8 ; fly - ash = 7.1 ; aggregate fine = 7.3 and split aggregate = 11 , with 20 % of superplasticizer . Used as a test specimen cylinders and beams for strength testing . Testing was conducted on the workability , flowability , and segregation . Blocking value ratio , and compressive strength testing will be a concrete value for this measure . Flowability testing , used lshaped box , j - ring test and v - funnel test while testing the workability with slump flow test used slump cone . Results obtained in the form of aggregate composition and compound of geoplolimer wrapped in bags to be used as an instant concrete Keywords: alkali solution, flowability, l-shaped box, self compactinggeopolymer concrete, slump flow